2022
DOI: 10.1002/anie.202214230
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymatically Gated Catalytic Hairpin Assembly Delivered by Lipid Nanoparticles for the Tumor‐Specific Activation of Signal Amplification in miRNA Imaging

Abstract: MicroRNA (miRNA) imaging in disease sites is vital to elucidate their role in cancer progression. However, limited tumor specificity remains a major barrier for traditional amplification approaches due to associated background signal leakage. Here, we report a generalizable approach via the combination of enzymatically triggered catalytic hairpin assembly with lipid nanoparticles (LNPs)-based delivery strategy for tumorspecific activation of signal amplification and therefore sensitive miRNA imaging. The sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 53 publications
(21 reference statements)
0
34
0
Order By: Relevance
“…As shown in Figure S13B, T-DNAzyme-treated HeLa and L02 cells both exhibited obvious green fluorescence signals, revealing the poor cell-type selectivity for T-DNAzyme. Quantitative results of average fluorescence intensity shown in Figure S13C revealed that the proposed E-DNAzyme/T-DNAzyme strategy exhibited an ∼3.36-fold discrimination ratio of tumor/normal cells, which is higher than the reported ∼2.0-fold and ∼2.6-fold values, respectively. , …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As shown in Figure S13B, T-DNAzyme-treated HeLa and L02 cells both exhibited obvious green fluorescence signals, revealing the poor cell-type selectivity for T-DNAzyme. Quantitative results of average fluorescence intensity shown in Figure S13C revealed that the proposed E-DNAzyme/T-DNAzyme strategy exhibited an ∼3.36-fold discrimination ratio of tumor/normal cells, which is higher than the reported ∼2.0-fold and ∼2.6-fold values, respectively. , …”
Section: Resultsmentioning
confidence: 68%
“…Quantitative results of average fluorescence intensity shown in Figure S13C revealed that the proposed E-DNAzyme/T-DNAzyme strategy exhibited an ∼3.36-fold discrimination ratio of tumor/normal cells, which is higher than the reported ∼2.0-fold and ∼2.6-fold values, respectively. 28,34 Because there is no absolute boundary between tumor and normal cells in complex biological tissues, the above results are still insufficient and unconvincing. Therefore, the ability of E-DNAzyme for tumor cell-specific molecular imaging was further investigated in the mixed cultivation of HeLa and L02 cells.…”
Section: Feasibility Investigation Of the Enzyme-activatedmentioning
confidence: 99%
“…For example, the APE1-controlled nanosensors were constructed through rational reengineering of conventional structure-switching nucleic acid probe by incorporation of a relevant activation unit. After the activation of sensing capability by APE1, diverse targets including metal ions, cytochrome c , and telomerase in cancer cells were fluorescence imaged. ,, Moreover, other disease-related molecules, such as ATP, microRNA (miRNA), and messenger RNA (mRNA), were detected with signal amplification manner by APE1 activated strategies with high cell-type selectivity, which was conducive to improve the signal-to-background ratio for tumor imaging through the “dual-keys-and-locked” concept. Meanwhile, the procedure of fluorescence imaging is simplified and the cost is reduced without exogenous factors.…”
Section: Introductionmentioning
confidence: 99%
“…Human apurinic/apyrimidinic endonuclease 1 (APE1) is a multifunctional enzyme that plays crucial roles in base excision repair and gene regulation. , As a base repair enzyme, APE1 recognizes and exerts an incision adjacent to 5′ of an abasic site, generating a nick in the phosphodiester backbone to initiate base repairing . APE1 is overexpressed in various cancer cells and has been identified as a diagnostic biomarker and therapeutic target. Intracellular imaging of APE1 would provide useful information for cancer diagnosis, prognosis, and treatment evaluation.…”
mentioning
confidence: 99%
“…Human apurinic/apyrimidinic endonuclease 1 (APE1) is a multifunctional enzyme that plays crucial roles in base excision repair and gene regulation. , As a base repair enzyme, APE1 recognizes and exerts an incision adjacent to 5′ of an abasic site, generating a nick in the phosphodiester backbone to initiate base repairing . APE1 is overexpressed in various cancer cells and has been identified as a diagnostic biomarker and therapeutic target. Intracellular imaging of APE1 would provide useful information for cancer diagnosis, prognosis, and treatment evaluation. Probes for measuring APE1 activities are generally designed based on APE1 cleavage-mediated separation of fluorophores and quenchers. To facilitate cellular entry, abasic site-containing DNA probes can be encapsulated with cationic polymers, , assembled on inorganic nanoparticles, , or tethered to DNA nanostructures .…”
mentioning
confidence: 99%